Points A , B , and C are lying on a circle centered at P such that A C intersects B P at D , where A D = 7 , ∠ A P B ( α ) = 1 2 0 ∘ , and 3 [ A D B ] = 2 [ A D P ] .
If the area of △ C P D can be expressed in the form c a b for positive integers a , b , and c such that a , c are coprime, and b is square-free, determine a + b + c .
Notation:
[
⋅
]
denotes the area of the figure.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given ratio of areas implies that P D = 5 3 A P as BP=AP. Using cosine formula on α = 1 2 0 ∘ of Δ A P D A P 2 + ( 5 3 ) 2 A P 2 + 5 3 A P 2 = 7 2 → A P = 5 . Hence PD=3, and CP=AP=5. Now the three sides of Δ B A D are AD=7, A B = 5 3 and BD=2, we get c o s ∠ B A D = 7 4 3 using cosine formula. Using the fact that angle at the center ∠ C P B is twice of the angle at the circumference ∠ B A D , we get c o s ∠ C P D = c o s ∠ C P B = 2 c o s 2 ∠ B A D − 1 = 4 9 4 7 giving s i n ∠ C P D = 4 9 8 3 . Now knowing the sides and sine of the included angle area is 2 1 ⋅ 3 ⋅ 5 ⋅ 4 9 8 3 = 4 9 6 0 3 thus the answer is 112.
We can easily prove that since A D divides Δ A B P into two triangles at a 3 : 2 ratio, then A D also divides B P by such proportion. That is, Δ A D B Δ A D P = D B D P = 2 3 . (See note below)
Let x be one fifth of the length of P B , so that D B = 2 x and D P = 3 x . From here we can express the areas of both triangles in terms of x .
By Heron's formula, we get the area of Δ A D P as:
Δ A D P = 4 1 − ( 2 5 6 x 4 − 3 3 3 2 x 2 + 2 4 0 1 )
In a similar way,
Δ A D B = 4 1 − ( 5 0 4 1 x 4 − 7 7 4 2 x 2 + 2 4 0 1 )
Equating these values to the ratio, and simplifying the equation, we get
4 4 3 4 5 x 4 − 5 6 3 5 0 x 2 + 1 2 0 0 5 = 0
( x 2 − 1 ) ( 4 4 3 4 5 x 2 − 1 2 0 0 5 ) = 0
x = ± 1 ; x = ± 1 8 1 7
Clearly, there are two positive values of x . However, only the value x = 1 conforms to the triangle inequality when substituted.
Now, substituting that, we get the dimensions for Δ A D P . We now draw an altitude from vertex P to A D at a point we'll name Q . From there, we can determine lengths D Q and A Q , using this.
9 − y 2 = 2 5 − ( 7 − y ) 2
Solving that gives y = 1 4 3 3 and 7 − y = 1 4 6 5 .
Now, we can find θ . I mean, cos θ .
cos θ = 1 4 1 3
From which we can derive
sin θ = 1 4 3 3
sin 2 θ = 9 8 3 9 3
cos 2 θ = 9 8 7 1
Now, going back to the circle. Observe that ∠ P A C ≅ ∠ P C A , so ∠ P C A = θ . It then follows that ∠ C P A = 1 8 0 − 2 θ . And ∠ C P D = 6 0 − 2 θ .
Now, we are equipped with all the necessary requirements for the area of Δ C P D .
Δ C P D = 2 1 c d sin P
= 2 1 ⋅ 3 ⋅ 5 ⋅ sin ( 6 0 − 2 θ )
= 2 1 5 ( sin 6 0 cos 2 θ − cos 6 0 sin 2 θ )
= 2 1 5 ( 2 3 ⋅ 9 8 7 1 − 2 1 ⋅ 9 8 3 9 3 )
= 2 1 5 ( 4 9 8 3 )
= 4 9 6 0 3
So, 6 0 + 3 + 4 9 = 1 1 2 .
Note:
If we look at P B as the base of Δ A P B , we can see that as well as for both triangles Δ A P D and Δ A B D , their heights are the same. So, their areas are directly proportional to the lengths of these bases, i.e., the lengths P D and B D .
Problem Loading...
Note Loading...
Set Loading...
Let the radius of the circle be r . Since △ A B D and △ A D P are sharing the altitude A E , this means that the areas of the two triangles are directly proportional to the base lengths that is:
D P B D ⟹ B D B D + D P 3 5 D P ⟹ D P = [ A D P ] [ A B D ] = 3 2 = 3 2 D P = r = r = 5 3 r Since 3 [ A B D ] = 2 [ A D P ] Note that B D + D P = r
By cosine rule , we have:
D P 2 + A P 2 − 2 ( D P ) ( A P ) cos α ( 5 3 r ) 2 + r 2 − 2 × 5 3 r × r × cos 1 2 0 ∘ 2 5 4 9 r 2 ⟹ r = A D 2 = 7 2 = 4 9 = 5
Let ∠ A C P = ∠ D A P = β and ∠ A D P = γ . By sine rule :
D P sin ∠ D A P 3 sin β = A P sin ∠ A D P = A D sin ∠ A P D = 5 sin γ = 7 sin α = 1 4 3
⟹ ⎩ ⎪ ⎨ ⎪ ⎧ sin β = 1 4 3 3 sin γ = 1 4 5 3 ⟹ cos β = 1 4 1 3 ⟹ cos γ = 1 4 1 1
Let P F be the altitude of △ P A C , then we have:
[ C P D ] = [ C P F ] − [ D P F ] = 2 1 ( C F ) ( P F ) − 2 1 ( D F ) ( P F ) = 2 1 C P 2 sin β cos β − 2 1 D P 2 sin γ cos γ = 2 5 2 × 1 4 3 3 × 1 4 1 3 − 2 3 2 × 1 4 5 3 × 1 4 1 1 = 4 9 6 0 3
⟹ a + b + c = 1 1 2